Avaliação da absorção colostral em neonatos ovinos da raça Bergamácia - Ulian, Carla Maria Vela [UNESP]; Fernandes, S. [UNESP]; Ramos, Paulo Roberto Rodrigues [UNESP]; Dias, Adriano [UNESP]; Lourenço, Maria Lucia Gomes [UNESP]; Chiacchio, Simone Biagio [UNESP] (Universidade Federal de Minas Gerais, Escola de Veterinária, 2014)
The period of absorption of colostrum macromolecules and the passive immunity transfer of Bergamacia lambs was determined. The serum proteinogram of lambs before the intake of colostrum up 48 hours of life and colostrum fractions between delivery and twelve hours after birth were measured. The total protein concentration in serum was evaluated by refractometry and also its relationship with the density and amount in colostrum. The serum concentration of gamma globulin in lambs from 0.111±0.07g/dL before the intake of colostrum was 1.609±0.72g/dL at 48 hours. In the colostrum samples, the concentration was 3.125±1.27g/dL immediately after delivery and 1.378±0.82g/dL twelve hours after birth. Serum total protein concentration increased from 4.46±0.58g/dL to 5.61±0.75g/dL between birth and after 48 hours, there was positive correlation with the density and total protein colostrum. The lamb had ascendant colostrum absorption subsequent to delivery, for twelve hours and then began its stabilization. The quantification of serum protein with the use of the refractometer in lambs can be used as a method to evaluate the transfer of passive immunity because it is directly related to the absorption of colostral gammaglobulin.

Objetivou-se determinar o período de absorção das macromoléculas colostrais e a transferência de imunidade passiva em cordeiros da raça Bergamácia. Avaliou-se o proteinograma sérico dos cordeiros antes da ingestão de colostro até 48 horas de vida e das frações colostrais ao nascimento e 12 horas pós-parto. Foi avaliada a concentração de proteína total no soro por refratometria e sua relação com a densidade e quantidade de gamaglobulinas presentes no colostro. A concentração sérica de gamaglobulina nos cordeiros variou de 0,111±0,07g/dL antes da ingestão de colostro a 1,609±0,72g/dL às 48 horas. Nas amostras de colostro, a concentração variou de 3,125±1,27g/dL, imediatamente após o parto, para 1,378±0,82g/dL, 12 horas após. A concentração de proteína sérica total teve acréscimo de 4,46±0,58g/dL para 5,61±0,75g/dL entre o nascimento e após 48 horas, apresentando correlação positiva com a densidade e a proteína total colostral. A absorção colostral pelo cordeiro foi ascendente até 24 horas subsequentes ao parto, quando, então, iniciou-se sua estabilização. A quantificação da proteína sérica, com uso de refratômetro nos cordeiros, pode ser usada como método para avaliar a transferência de imunidade passiva, pois está diretamente relacionada com a absorção de gamaglobulina colostral.
Evaluation of colostral absorption in neonates of Bergamacia breed
Keywords: Cordeiros; Eletroforese; Gamaglobulina; Transferência de imunidade passiva; Electrophoresis; Immune passive transfer; Gammaglobulin; Lamb